A Mathematical Model of Microplastic Spreading into Fish Digestive Based On Abiotic Factor - Zani Anjani Rafsanjani HSM; Nurul Suwartiningsih; Ichsan I Luqmana (Jurnal Fourier, 2021)
In this research, we observe the fish from seven different river location on Yogyakarta by evaluating its digestive weight. We investigate the microplastics spreading on fish digestive based on the abiotic factor such as river temperature, acidity, and river flow microplastics granules to be carried into the digestive tract of the fish. The rate of microplastics in the fish body can be describe mathematically using differential equation. We build a model based on the diagram flow of the relationship between each variables. Thus we have a differential system as the model. In the next step we analyze the model analytically. To show the accurancy of the model, we make a simulation using data simulation to the system and we compare it with the computing results using observation data. At the end of our research, we give a justification for the most influential abiotic factor for microplastic sreading.